Ett internt perspektiv på redovisning av leasing : En fallstudie över Gällivare Kommun - Nedergård Zetterqvist, Hanna; Utsi, Emilia (2011)
Previous research has mainly focused on the design of external accounting regarding leasing while the internal perspective has not gained as much attention (Finnerty, Fitzsimmons & Oliver, 1980; Goodacre, 2003; Wilkins & Zimmer, 1983). Consequently, the purpose of this essay is to examine the problems that can arise internally within the local government. The focus is more specifically on the process of setting up leasing contracts and how these are managed within different departments within a local government.Our study is based on a qualitative approach where the focus is on the actors’ view of the process of setting up leasing contracts. Interviews have been made with actors from different parts of the local government. The main conclusion of this essay is that unclear accountability, lack of communication and a disregard about the financial implications exist due to shortage of routines. Therefore suggestions are made on how routines can be designed within the local government. Validerat; 20110720 (anonymous)